United for progress: Ghana’s multi-institutional circular bioeconomy Innovation Hub - Agbefu, Dzifa; Drechsel, Pay; Amoah, Philip (RUAF Foundation, 2024)
After years of fragmented efforts to create circular approaches to waste management in Ghana, the new circular bio-economy (CBE) Innovation Hub in Ghana is bringing together diverse stakeholders to jointly promote existing CBE approaches through training, advice, demonstrations, and research, while fostering the development of new, accessible innovations.